1994
DOI: 10.1111/j.1467-8624.1994.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Out of Home in a Kibbutz Communal Arrangement: It Makes a Difference for Infant-Mother Attachment

Abstract: SAGI, ABKAM \M, \ VN IJ/LNDOOHN, M UUNUS H Avii ζι κ, ΟΗΛ DOSNLLI , FUVNK and M > OUVA Sleeping Out of Home in a Kibbutz Communal Arrangement It \iakes a Difference for Injant-Mother \ttacninent CIÜLD Dt VLLOPMLNM , 1994,65,992-1004 Att ichment classific.Uion distributions oi mlant-mothei dyads hvmg in 2 tvpes of Isiaeh kibbut7im wtre comp.utd The subjects weie 48 uiiants, 14-22 months old (M = 18 29 months) 13 bovs and 10 girls were from 23 kibbut.7 infants houses with communal sleeping arrangements ind 13 bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 23 publications
4
54
1
1
Order By: Relevance
“…Thus, it seems that repeated exposure to nightly separation, an integral feature of the communal sleeping arrangement and not the experience of group child care early in life per se, is a significant risk factor to the development of attachment in- security. This proposition accords with a similar conclusion of earlier research with infants raised in communal sleeping arrangements (Sagi, Lamb, Lewkowicz, Shoham, Dvir, & Estes, 1985;Sagi, van IJzendoorn, Aviezer, et al, 1994).…”
Section: Ecological Variation and Socioemotional Developmentsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, it seems that repeated exposure to nightly separation, an integral feature of the communal sleeping arrangement and not the experience of group child care early in life per se, is a significant risk factor to the development of attachment in- security. This proposition accords with a similar conclusion of earlier research with infants raised in communal sleeping arrangements (Sagi, Lamb, Lewkowicz, Shoham, Dvir, & Estes, 1985;Sagi, van IJzendoorn, Aviezer, et al, 1994).…”
Section: Ecological Variation and Socioemotional Developmentsupporting
confidence: 92%
“…From the attachment paradigm it appeared that the kibbutz practice of communal sleeping for children created an environment that deviated from what might be considered desirable for healthy emotional development . In a recent study (Sagi, van IJzendoorn, Aviezer, Donnell, & Mayseless, 1994), kibbutz infants in the communal sleeping arrangement showed low incidence of secure attachment (48%) compared with the Ainsworth and colleagues (Ainsworth, Blehar, Waters, & Wall, 1978) normative sample (all the insecure infants were ambivalent). In comparison, kibbutz infants in the familial sleeping arrangement showed a high frequency of secure attachment patterns (80%).…”
Section: The Kibbutz Ecology and Separation Experiencesmentioning
confidence: 80%
See 1 more Smart Citation
“…Most of the insecure infants in the day-care context were anxious/ ambivalent. This last finding, namely predominance of the anxious/ambivalent pattern among insecure infants, reflects a consistent pattern in Israel (Sagi et al, 1985;Sagi, van IJzendoorn, Aviezer, Donnell, & Mayseless, 1994). The present study explored two aspects of the child-care situation: (1) the number of hours the mother worked away from home and (2) the type of substitute care employed, namely one substitute caregiver or a group day-care situation.…”
Section: Introductionsupporting
confidence: 66%
“…This social-cultural context may be unique. For example, in a series of studies conducted by Sagi and his colleagues, it was demonstrated that the vast majority of insecure infants in Israel are ambivalent (Sagi et al, 1985(Sagi et al, , 1994. This poses a question about whether the meaning of ambivalent attachment in Israel is similar to ambivalence in other cultures (Sagi, van IJzendoorn, & Koren-Karie, 1991).…”
Section: Discussionmentioning
confidence: 99%